Torturing the new barbarians - Cox, Rory (Contesting torture, 2023)
This chapter reflects on the ways in which language and history have influenced both debates about torture and its employment by Western states since 2001. Primarily, it argues that the image and trope of the barbarian has played a central role in shaping discourses of terrorism. As terrorists have become the ‘new barbarians’ of the modern era, this has shifted expectations on how such individuals – characterized as fundamentally and existentially opposed to ‘civilization’ – can or should be treated. It argues that one of the most deleterious effects of this rhetoric of barbarism is that terrorists, or even those suspected of terrorism, have been subjected to illegal torture practices. Referring to the work of ontological security studies, the chapter attempts to explain why the barbarian metaphor is so attractive to developed states when confronted by the threat of modern terrorism. While the chapter focuses principally on the United States and the United Kingdom, it also highlights the pervasive spread of the connection between terrorism and barbarism across the international community.